A feasibility study on the laboratory-scale production of "sotanghon" (Chinese vermicelli) - Ong, Rosita B.; Gatchalian, Miflora M. (1972.)
ABSTRACT The study hoped to determine the feasibility of producing "sotanghon" on a laboratory scale using improvised equipment and to point out the major problems that could arise from "sotanghon"-production under local situation. To achieve this, a laboratory procedure for "sotanghon" - manufacture using improvised equipment was set-up and the product arrived at from this procedure evaluated in terms of objective tests and sensory evaluations relative to other "sotanghon" products available in the market. Results of the study showed laboratory-scale production of "sotanghon" using improvised equipment to be feasible. Although very limited in terms of yield, a "sotanghon" product of desirable cooking quality was produced using the improvised laboratory scale method. However, the major problems in the procedure were the high operational and labor cost and the inefficiency in the extraction method for starch. The latter may explain the low yield and the pigmentation of the "sotanghon".
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Noodles; Sotanghon; Pasta products